A Comparative Study on the Effect of Hygrothermal Exposure over the Mechanical Strength of Glass Fiber and Hybrid Fiber Reinforced Polyester Composites - Manisaran, N.; Santhan, G.; Meenakshi, C.M.; Krishnamoorthy, A. (Asian Journal of Chemistry, 2019)
A composite material is a combination of two or more different materials and it plays a vital role in a wide range of applications. In automotive and mechanical industries the demand for lighter weight components is increasing day by day. Glass and flax reinforced composites have superior properties such a high tensile strength at any weather conditions. As the composite materials are used in many applications and exposed to harsh environment, the water molecules from the environment may induced in to the material then reinforcements may be affected and which causes damage to the interface bonding. In this work the effect of hygrothermal environment on hybrid fiber reinforced composites are studied, two types of composite laminates are prepared one is glass fiber reinforced composite (GFRC) and the other is glass and flax fiber reinforced hybrid composite (HFRC). Tensile test samples are cut from the laminates prepared as per ASTM D 638 standard and the tensile strength values before and after hygrothermal exposure are identified and compared from the result it is presumed that hybrid materials are showing better resistance towards hygrothermal behaviour compare to mono glass fiber composites.